THE IMPLEMENTATION OF COOPERATIVE LEARNING TYPE THINK PAIR SHARE MODEL TO IMPROVE READING COMPREHENSION SKILL IN DISRUPTION ERA - Latief, Maullana; Sriyanto, Muhammad Ismail; Daryanto, Joko (Universitas Sebelas Maret, 2018)
The purpose of this research was to improve the skill of reading comprehension by applied Think Pair Share (TPS) model in disruption era for fifth grade students in SDN Purwotomo No. 97 Surakarta on academic year of 2017/2018. The form of this research was a Classroom Action Research which conducted in two cycles. Each cycle consisted of four stages i.e. planning, action, observation, and reflection. The subjects of this research included teacher and 23 fifth grade students in SDN Purwotomo No. 97 Surakarta. The data collected by observation, interview, test, and documentation techniques. The data validity test were using content validity, triangulation of resource, and triangulation of technique. The result of this research shows the improvement of skill of reading comprehension values from pre-action, cycle I until cycle II.